Rahsaan Roland Kirk live in '63 & '67 - Peck, David; Galloway, Phillip; Gulotta, Tom; Kirk, Rahsaan Roland, 1936-1977; Gruntz, George; Burton, Ron; Pedersen, Guy; Ørsted Pedersen, Niels Henning, 1946-2005; Humair, Daniel; Riel, Alex (Jazz icons., 2008)
Performances featuring the jazz musician, originally filmed for the Belgian television program, Jazz pour tous, and the Dutch television program, Rolando, and at the 1967 Kongsberg Jazz Festival.